The implementation of the system of lifelong learning - Volkov, S. (Problems of Engineer-Pedagogical Education, 2021)
The article considers the genesis of viewpoints regarding the definition of the terms "continuing education", "lifelong learning", and “adult education". The essence of lifelong learning, which consists of life-long learning, life-wide learning and self-motivation to learn, is revealed in detail. The four terms of continuing education are proposed on the basis of the literature reviews: lifelong learning, adult education, continuing vocational education and online courses. The differences between formal, non-formal and informal learning are highlighted. The state of the development of lifelong learning in the European Union, the trends in continuing education of the population aged 25-64, the growth of the EU spending on adult education and training, the peculiarities of European legislation in the field of adult education have been analyzed. The legal framework of Ukraine regarding continuing education has been studied. According to the considered documents, one of the leading directions of the development of adult education is digitalization of education. The availability of Web 2.0 technologies has significant potential to support lifelong learning efforts, enabling non-formal, timely and everyday learning. The article identifies the most modern, convenient and affordable form of lifelong learning, which is learning by means of online courses. The analyses of the most popular global massive open online education platforms, the growing trends in the number of such platforms in the period from 2016 to 2018, their users and the number of online courses, which are placed on such platforms, have been carried out. Examples of Ukrainian open online educational platforms with the largest number of online courses are given. The article concludes that Ukrainian specialists need to improve their professional competencies, improve their skills in a convenient informal format. There is a need in Ukraine to develop a system of nonformal adult education focused on the use of the latest information and communication technologies, in particular the development of a system of online courses.